THE EFFECT OF DIFFERENT LEVELS OF FISH MEAL ( Scyllium Canicula ) IN THE BROILER DIETS UPON THE INCIDENCE - E.A.Al-Naemi‎, Mohammed; A.Saleh ‎, ‎ Ahmed; M.Razuki, Waleed (The Iraqi Journal of Veterinary Medicine, 2025)
This experiment was conducted to determine the effect of different levels of fish meal on the incidence of gizzard lessions and ulcerations and percentage of mortality. A totla of 348 day old chicks were randomaly assigned to the three treatment (treatment represent 0.0 , 6.6 and 13.3% fish meal ) with four replicates per treatment. Chicks were fed ad libitum from day-old to 7 weeks of age.The results of this experiment indicated that the correlation coefficients between scores of infection severity and body weight, weight gain , feed intake and feed conversion ratio was —0.750, -0.750, -0.494 and 0.177 at 4 weeks of age, but it was -0.877 , -0.858 , -0.764 and 0.795 at 7 weeks of age respectively.The percentage of infection was 0.0 , 25 and 75% While, the infection severity was 0.0 , 1.3 and 3.0% . However, percentage of mortality was 1.80 , 5.0 and 12.5% for birds fed on diet containing 0.0 , 6.6 and 13.5 % fish meal respectively.It can be concluded that the increasing this kind of fish meal in the diet up to 13.3% 1ed to depressed broiler performane due to gizzerosine factor, which is resulting from the high temperature that had been used in fish meal processing.